Are there any differences on sensory and physicochemical attributes of pre- and post-rigor broiler meat? - Khatun, R; Akter, I; Deen, RA; Ghosh , D; Hashem, MA (Meat Research, 2025)
This study investigated the differences in sensory and physicochemical attributes between pre- and post-rigor broiler meat. Five live broilers were collected from the K.R. Market of BAU, Mymensingh, and meat samples were analyzed immediately after slaughter and deboning for pre-rigor conditions, while post-rigor samples were analyzed after 24-hour chilling at 4°C. A 2×2 factorial experiment in a completely randomized design (CRD) was employed for data analysis. Sensory parameters, including color, flavor, texture, tenderness, and overall acceptability, were assessed, along with physicochemical properties such as pH, cooking loss, drip loss, water-holding capacity, and instrumental color measurements (CIE L*, CIE a*, CIE b*, hue angle, and saturation index). The results revealed that sensory attributes of both breast and thigh meat improved significantly (p<0.05) after post-rigor aging, indicating better flavor, tenderness, and overall acceptability. Physicochemical analysis showed a significant decrease (p<0.05) in pH for both breast and thigh meat, while instrumental color analysis indicated that post-rigor breast meat had significantly higher CIE L* (lightness) and hue angle but lower CIE a* (redness). These findings highlight that post-rigor aging significantly enhances both sensory and physicochemical qualities, making it the more preferable and acceptable treatment. This study provides valuable insights for optimizing meat processing methods to improve consumer satisfaction and meat quality.